1985
DOI: 10.1159/000173873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verapamil and Bepridil on Occlusion and Reperfusion Arrhythmias in the Canine Heart

Abstract: The effects of verapamil and bepridil on occlusion and reperfusion ventricular arrhythmias including ventricular fibrillation (VF) were studied in a canine model. The control group consisted of 27 dogs. 30 dogs received intravenous verapamil (0.2 mg/kg/3 min followed by a continuous infusion of 0.01 mg/kg/min for 15 min). 18 dogs received bepridil (0.5 mg/kg/min for 10 min). The left anterior descending coronary artery was occluded in one step 8 min after the commencement of verapamil administration and 5 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Bepridil prolonged the ERP of infarcted myocardium to a greater extent (15 %) compared to normal tissue (9 %) [365]. On the contrary, bepridil in the same dose (5 mg/kg) administered to dogs during coronary occlusion proved to be arrhythmogenic but it must be noted that bepridil administration during the reperfusion period absolutely prevented VF [133]. In canine Purkinje fibers, 1-10 µM bepridil evoked EAD at long CL but the triggered activity was rare [131].…”
Section: Human Data On Hemodynamic Effects Of Monatepilmentioning
confidence: 93%
See 1 more Smart Citation
“…Bepridil prolonged the ERP of infarcted myocardium to a greater extent (15 %) compared to normal tissue (9 %) [365]. On the contrary, bepridil in the same dose (5 mg/kg) administered to dogs during coronary occlusion proved to be arrhythmogenic but it must be noted that bepridil administration during the reperfusion period absolutely prevented VF [133]. In canine Purkinje fibers, 1-10 µM bepridil evoked EAD at long CL but the triggered activity was rare [131].…”
Section: Human Data On Hemodynamic Effects Of Monatepilmentioning
confidence: 93%
“…Bepridil was also reported to evoke EAD at long cycle length (CL) in canine Purkinje fibers [131] and it also increased TDR by mainly lengthening M cell APD in canine wedge preparations [132]. Moreover, in vivo animal studies reported arrhythmogenic action of bepridil during coronary occlusion (but not during reperfusion) [133], [134]. VT, prolongation of QTc interval and TdP were detected with bepridil treatment in permanent AF patients, while no ventricular arrhythmias were seen with amiodarone [134].…”
Section: Proarrhythmic Actions Of Ccasmentioning
confidence: 99%
“…Dantrolene significantly reduced the frequency and duration of episodes of ventricular fibrillation after coronary artery ligation in rats 13 but another early study suggested that pretreatment with dantrolene actually increased the frequency of ventricular fibrillation induced by coronary artery occlusion in dogs. 14 More recent studies demonstrated that dantrolene prevents abnormal calcium leak in both malignant hyperthermia RyR1 15 and CPVT RyR2 16 channels. In vitro , a CPVT mutant channel (R2474S) was shown to decrease the threshold at which luminal calcium elicited RyR2 channel opening, and thereby induced calcium “sparks” and delayed afterdepolarizations (DADs); 17 in mice with this mutation, dantrolene stabilized the channels and was antiarrhythmic.…”
Section: Dantrolene As An Antiarrhythmicmentioning
confidence: 99%
“…Whether chronic therapy would be feasible would require a lot more work: in the Zamiri experiment, pretreatment was beneficial in isolated rabbit hearts, but pretreatment also exacerbated arrhythmias in earlier dog studies. 14 …”
Section: Where To Next?mentioning
confidence: 99%
“…Dantrolene has previously been described as an inhibitor of arrhythmias in animal models of ischemia-reperfusion [33][34][35] . More recently, dantrolene was demonstrated to inhibit catecholaminergic polymorphic ventricular tachycardia in a knock-in mouse model heterozygous for mutation R2474S in RyR2 [36] (Figure 1).…”
Section: Dantrolenementioning
confidence: 99%